Kajian Media Online: Best Practice Manajemen Badan Usaha Milik Desa Dalam Menciptakan Ekonomi Inklusif : Kasus BUMDES Ponggok Tirta Mandiri Klaten Jawa Tengah - Ami Purnamawati; Yuanita Indriani (Coopetition : Jurnal Ilmiah Manajemen, 2021)
One of Indonesia policies to strengthen village economy is founding a village company owned by a smallest local government as the implementation of the Law No 32/2004 concerning Regional Administration. As the new economic institution, some villages still face many obstacles for understanding and implementing the law, finding business ideas, not to mention human resources as well as effective management. Ponggok Village managing its company effectively and creating inclusive economy is urgent to study as the best practice. It manages some business units (fish pond rent, convention hall, event organizer, mini market, family tourist attraction and underwater tourist attraction). In 2018 Tirta Mandiri – the name of the company - gained 16 billion rupiahs. It relies on the underwater attraction, as the main income. By using qualitative method, the online media news contents of the success were analyzed. The results show the potencies of initiating the water attraction business are the political will of the village head, natural resources and cooperation with a university; while people awareness, limited human resources and financial capital are the obstacles. The milestone of underwater attraction popularity begins by a visitor’s promotion on social media and other effective managements are the cooperation with a bank and implementation of people ownership policy. Those cause some progressive outputs which are the business management is getting improved; therefore it can hire more employees, is able to complete the facilities, and to conduct people welfare based programs. For maintaining the developed business existence, the stakeholders’ commitment, competence, consistence and creativity must be put on the first place.